An in-depth look at the status of environmental financial accounting in Mexico from the point of view of stakeholder theory: myth or reality? - Martínez, Saulo Sinforoso; Mesa, Arístides Pelegrin (Review of Business Management, 2021)
Purpose – This research project analyzes the use of the theoretical contributions regarding environmental financial accounting (EFA) by Mexican companies. Design/methodology/approach – The methodology is divided into two sections. The first part involves a document analysis of the sustainability reports issued by 29 sustainable companies from the Mexican Stock Exchange. The second section describes the correlation between the EFA components and revenue. Findings – The preliminary findings show that the ideas regarding social and environmental accounting written over two decades ago by Gray (1992), Laringa (1995), Moneva and Llena (1996), Bebbington (2001), and Llull (2001), among others, have been applied within the context of the Mexican economy. However, there are some theoretical gaps that will continue to make EFA a myth for emerging economies due to the lack of public policies. Originality/value – This study identifies that the Mexican economy requires two actions in order to legitimize the stakeholder theory. First, the concepts of environmental accounting need to be applied across micro, small and medium-sized businesses. Second, the relationships among stakeholders (suppliers, customers, shareholders, etc.) need to be analyzed in the environmental reports in order to assess their level of influence on decision making. The starting point for this analysis should be the methodology applied in developed economies.